The relative significance of iron-binding and aluminium-binding of phosphate in soils representative of the main New Zealand genetic groupings as revealed by fractionation methods and by phosphate fixation studies in the laboratory : a thesis presented in partial fulfilment of the requirements for the degree of Master of Agricultural Science (Horticulture) - Goh, Kuan M (Massey University, 1962)
Although a great body of evidence points to the presence of Iron - and aluminium - bound phosphate in soils as products of the phosphate fixation prooess, until recently no satisfactory procedures have been available for the quantitative assessment of the amounts of these forms in soils. Chang and Jackson (1957) were the first workers to propose a scheme of phosphate fractionation, which included the separate determination of iron - and aluminium - bound phosphates. The limitations of their procedure have been discussed by Fife (1959a, 1959b and 1962), who has proposed (1962) a modified method for the determination of the aluminium - bound soil phosphate fraction. Fife (unpublished results) has subsequently incorporated this procedure into a general scheme of soil phosphate fractionation, which includes the selective determination of iron - bound and calcium - bound phosphates.[FROM INTRODUCTION]
Keywords: Phosphates; Soils; Analysis; New Zealand